Poor outcomes for double‐hit lymphoma patients treated with curative‐intent second‐line immunochemotherapy following failure of intensive front‐line immunochemotherapy. (5th December 2019) - Landsburg, Daniel J.; Ayers, Emily C.; Bond, David A.; Maddocks, Kami J.; Karmali, Reem; Behdad, Amir; Curry, Madeira; Wagner‐Johnston, Nina D.; Modi, Dipenkumar; Ramchandren, Radhakrishnan; Assouline, Sarit E.; Faramand, Rawan; et al.
Summary: While patients with double‐hit lymphoma (DHL) are now frequently treated with intensive front‐line immunochemotherapy, outcomes for those who fail these regimens and subsequently receive curative‐intent second‐line immunochemotherapy are unknown. We identified 55 such patients who achieved an overall/complete response rate of 29%/11%, median progression‐free/overall survival (PFS/OS) of 2/5·1 months and one‐year PFS/OS of 10/19% following the start of second‐line therapy. These outcomes may serve as a standard against which future second‐line treatment strategies for relapsed/refractory DHL can be measured and justify investigation of non‐cytotoxic therapies in the second‐line setting for these patients.